1988
DOI: 10.1002/mawe.19880190607
|View full text |Cite
|
Sign up to set email alerts
|

Production of stainless steel filters by liquid phase activated Gravity sintering

Abstract: Production of stainless steel filters by sintering the loose powders offers difficulties due to the stable oxide layers covering the particles and preventing formation of sintering necks. Boron compounds, i.e. NiB and BN, were found to activate sintering by both reducing the oxide layers and forming a liquid phase. The resulting samples offer excellent mechanical properties, in particular high ductility, as well as satisfactory permeability, while the corrosion resistance is not lower than with boron‐free stai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 2 publications
0
17
0
Order By: Relevance
“…For gravity sintered filters it has been shown that even relative large amounts of boride eutectic do not do any harm as long as they are isolated, i.e. concentrated at the sintering necks [22]. As soon as however this boride eutectic forms a continuous network in the sintered body, severe embrittlement occurs.…”
Section: Mechanisms Of Sintering Activation and Drawbacksmentioning
confidence: 99%
“…For gravity sintered filters it has been shown that even relative large amounts of boride eutectic do not do any harm as long as they are isolated, i.e. concentrated at the sintering necks [22]. As soon as however this boride eutectic forms a continuous network in the sintered body, severe embrittlement occurs.…”
Section: Mechanisms Of Sintering Activation and Drawbacksmentioning
confidence: 99%
“…9). The presence of nitrogen inhibits eutectic reactions between iron and iron boride, but enhances the reactions between boron and nitrogen, resulting in the formation of an inert phase that does not improve the sintering rate (on the other hand, BN is used for the activation of sintering in vacuum [9]). There was therefore no improvement in measured mechanical properties.…”
Section: Sintering In Nitrogen Atmospherementioning
confidence: 99%
“…The compaction pressure was applied normally to compound. [11,12,13] In a few investigations only, elemental the dilatometry direction, i.e., the direction along which boron was used. [9,10,14] German et al, [14] as an example, used dimensional changes were measured.…”
Section: Introductionmentioning
confidence: 99%